Dietary Assessment for Meals of Nurseries Children in Baghdad City (Baghdad Science Journal, 2008)
The objective of this study was to assess the nutritional status of childs of nurseries in Baghdad city so that an early detection of malnutrition cases could be carried out. The results revealed that the daily consumption of food calories, protein, fat and carbohydrate were 1180.5 calories, 27.2gm, 38gm and 180gm, respectively, which were less than the RDA values and the percentages of these nutrients supplied by the food intake were 90.8, 83.7, 87.3 and 90.3%, respectively. It was also demonstrated that the highest percentages of stunting, underweight and wasting, which amounted to 32, 22.7 and 1.5%, respectively, were among those childs who obtained inadequate calories, while the percentages of the forementioned malnutrition cases among those childs who obtained inadequate calories were 7.5, 4.5 and 3%, respectively. The results also pointed out that the general nutritional pattern of the childs food style in this study was strictly and unbalanced due to the lack in food meals recommended to be taken daily of certain main food groups according to the food guide pyramid for young children, such as meats, poultry, fish, eggs, legumes,nuts as well as vegetables and fruits group, otherwise, the food consumed was stricted to milk,yogurt and cheese group ,vegetables and fruits group, bread, rice, and other cereals as well as their products and bakeries. There was anumber of bad food habits among the children of research sample was also observed and was found effect the quantity and quality of food consumed.